Physico-chemical characterization of the residual cake of D-004 production: lipids extract of the Roystonea regia fruits.Technical note - Morales, Carmen L.; Gonz?lez, V. L.; Marrero, D.; Rodr?guez, E. A.; Sierra, Roxana S.; Vicente, Roxana (Cuban Journal of Agricultural Science, 2013)
The physico-chemical characteristics of the residual cake (RC) obtained from the production of the D-004 were determined. The 61.9 % of the cake was formed by particles between 2.36 and 0.5 mm. Its main proximal composition was the following: humidity (8.70 %), crude protein (9.50 %), crude fiber (31.57 %), ash (6.46 %) and fat (0.77 %), mainly composed by the fatty, palmitic, lauric and myristic acids. The total content of polyphenols was 1.53 ? 0.02 mg/100 g. The elemental composition (ppm) included: Ca (3983 ? 48), Na (938 ? 9), Mg (1967 ? 14), K (10492 ? 151), Fe (42.07 ? 0.6), Zn (19.1? 0.1), Mn (10.3 ? 0.6), Pb (< 0.5), Co (< 0.5) and Cd (< 0.1). The physicochemical characteristics of the RC from D-004 production are a source of macro and micronutrients. These preliminary results sustain the development of further studies to determine the possible application of this RC in swine feeding. Key words: D-004 by-product, palm tree nut, palm tree, chemical composition.